Interelement Decoupling Strategies at UHF MRI - Zivkovic, Irena (Frontiers in Physics, 2021)
Moving to the ultra-high field magnetic resonance imaging (UHF MRI) brought many benefits such as potentially higher signal-to-noise ratio, contrast-to-noise ratio and improved spectral resolution. UHF MRI regime also introduced some challenges which could prevent full exploitation of mentioned advantages. Higher static magnetic field means increase in Larmor frequency which further implies the shorter wavelength in a tissue. The shorter wavelength causes interferences of the RF signal and inhomogeneous excitation which partially can be resolved by introduction of the multichannel coil arrays. The biggest problem in UHF multichannel densely populated arrays is existence of the interelement coupling which should be minimized as much as possible. This manuscript presents the non-conventional, recently developed decoupling techniques used in UHF MRI.